Understanding the Role of Key Stakeholders and the Challenges in Developing Shariah-compliant Medical Tourism in Malaysia: A Legal Perspective - Mohamad Amin, Noor Shuhadawati; Ramli, Noriah; Zawawi, Majdah (Kanun: Jurnal Undang-undang Malaysia; Vol 36 No 1 (2024): Kanun: Jurnal Undang-undang Malaysia Volume 36 Number 1 January 2024DO - 10.37052/kanun.36(1)no1, 2023)
The search for healthcare treatment tailored to religious and ethical beliefs has gained popularity in the changing medical tourism environment. This study examines the complexities of Shariah-compliant medical tourism in Malaysia, emphasizing on the critical role of stakeholders in a comprehensive legal framework. The methodology adopted for this study is doctrinal. An important issue that has arisen is the lack of engagement between healthcare providers and appropriate government organisations in developing Shariah-compliant medical tourism. This study initially identifies relevant stakeholders who promote Shariah-compliant medical tourism. It then analyses the role of relevant government agencies, healthcare providers and religious scholars in addressing this topic, alongside legal concerns and religious requirements. This research examines the obstacles and potential in aligning medical tourism practices with Shariah principles. An investigation into the involvement of stakeholders in the legal framework highlighted the critical need to harmonise Islamic principles and modern healthcare services, thus supporting the development of Shariah-compliant medical tourism in Malaysia. This study recommends the formation of a Shariah Advisory Committee to oversee the stakeholders. This committee will ensure that all key stakeholders are not only consulted, but also play an active role in advising government agencies on important policies and measures through integrated research. This cooperative strategy aims to bridge the gap between JAKIM as a responsible institution with relevant ministries and healthcare providers, in addition to promoting this sector globally. This committee is expected to create a synergistic environment that increases the profile of Shariah-compliant medical tourism in Malaysia. Keywords : Medical tourism, shariah-compliant, stakeholders, challenges, JAKIM, Malaysia Full text : PDF